Sharia-Ethical Self-Identity and Sustainable Brand Loyalty: The Nexus of Green Brand Love - Sari, Ajeng Herliyana; Kuswati, Rini (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2026)
Purpose – This study aims to analyze the role of the Social Self and Inner Self in shaping Brand Loyalty through the mediation of Green Brand Love in the context of sustainable Islamic marketing. This study stems from increasing consumer awareness of environmental issues and the need to integrate ethical and spiritual values into consumption behavior. Method – A quantitative approach was employed, collecting data from 160 respondents in Indonesia (atau lokasi spesifik lainnya) selected via purposive sampling. The data were analyzed using Structural Equation Modeling (SEM-PLS) to ensure robust testing of the measurement and structural models, including mediation effects. Findings – The results demonstrate that both Social Self and Inner Self are powerful predictors of Green Brand Love, which in turn acts as a crucial mediator in strengthening Brand Loyalty. Notably, the Inner Self shows a deeper connection to green values, suggesting that personal ethics are fundamental to sustainable brand attachment. Implication – These findings provide a theoretical bridge between self-identity theory and green marketing within the framework of Islamic management. Practically, firms should align their branding strategies with consumers’ ethical and social identities to foster genuine loyalty toward sustainable initiatives, thereby contributing to the achievement of Sustainable Development Goals (SDGs)